Accounting Performance and Sustainable Competitive Advantage in Indonesian Mining Companies - Suswandoyo, M. Imam; Sumaryo (JOURNAL INTELEKTUAL, 2023)
Introduction/Main Objectives: To investigate the accounting performance of Investment Opportunity Set, Company Size, Profitability and Debt to Equity Ratio to the Sustainable competitive advantage of Mining Companies in Indonesia for the 2018-2021 period. Background Problems: The phenomenon of sustainable competitive advantage in Indonesian mining companies has not been a priority in various corporate accountability strategies to stakeholders Novelty: Use of performance-based Sustainable competitive advantage variables in accounting with stakeholder theory and agency theory approaches. Research Methods: This study uses secondary data from Indonesian mining sector companies for the 2018-2021 period, using a purposive sampling method, and data analysis using SPSS version 25. Finding/Results: Accounting performance with Profitability and Debt to Equity Ratio has a significant positive effect on Sustainable Competitive Advantage, but the Investment Opportunity Set proxy has no effect on company size. Conclusion: Accounting performance can be used to measure sustainable competitive advantage. The implication is that management must pay attention to accounting performance in achieving sustainable competitive advantage.